Clothing as an Expression of Women Writers' Individuality and Women's Journals as Advisers and Arbiters of Clothing (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The way three Serbian female writers (Milica Stojadinović, Jelena Dimitrijević and Isidora Sekulić) treated clothing, and the way in which the women’s magazines at the beginning of 20th century wrote about dresses or hats, tell а lot about social status, and cultural and social qualification. Clothing displays dependence and slavery, but also a release, it articulates sex differences, and most of all, it is the reflection of individuality and a personal attempt to mark one’s place in society.
Keywords: Clothing аnd individuality; Jelena Dimitrijević; Isidora Sekulić; women’s magazines